High Altitude Illness: Dietary Implications. Issue 1 (January 2016) - Morin, Karen H.
Abstract : Have you ever wondered how to prevent high altitude illness when traveling? What is the best nutrition advice for patients planning travel to a high altitude destination? Our nutrition expert, Dr. Morin, explains how adequate hydration and eating more complex carbohydrates may be helpful as proactive preventative measures.